FUNCTIONS OF ENSURING INFORMATION SECURITY OF PUBLIC ADMINISTRATION IN UKRAINE IN THE FACE OF FULL-SCALE ARMED AGGRESSION OF THE RUSSIAN FEDERATION - Onopriienko, S. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The purpose of the article is to define the concept and functions of ensuring the information security of public administration in Ukraine in the conditions of full-scale armed aggression of the Russian Federation. The definition is proposed for the functions of ensuring the information security of public administration in Ukraine: these are the methods inherent in the activities of public administrations to preserve their own functionality in the face of destructive information influences and prevent harm (danger) to the information rights and interests of a person, civil society, bodies, enterprises, institutions and organizations and the state generally. Based on the content analysis of the activities of public administrations in the information sphere, the following stages of implementation of the functions of ensuring information security of public administration have been identified: 1) statements and generalizations; 2) analysis; 3) modeling; 4) regulatory consolidation; 5) practical implementation; 6) reflection and evaluation. These stages are characterized. The substantiation of the thesis is given that the functions of ensuring information security of public administration can be classified according to different criteria, but it is more appropriate to classify according to the criterion of effectiveness. The classification is proposed, which includes: the function of maintaining information sovereignty, the function of informing the international community about the enemy's violation of the laws and customs of war, causing harm to the health, life and property of the civilian population; the function of educating a high level of information culture; consolidation function. The characteristic is provided by the specified functions. Features are defined for the implementation of these functions in the conditions of the legal regime of martial law. The conclusion is made that the functions of ensuring the information security of public administration are one of the priorities among other functions of ensuring national security. Arguments are given that the ability of Ukraine to withstand and effectively resist Russian aggression significantly depends on the ability and successful application of the function of informing the international community about the enemy's violation of the laws and customs of war, causing harm to the health, life and property of the civilian population. In addition, the function of educating a high level of information culture remains relevant, which makes it impossible for the enemy to have a destructive influence on the life of the state and civil society.
Keywords: information security, state security, functions, stages, information legal relations, full-scale armed aggression of the Russian Federation